Enterprise Resource Planning Implementation to Improve Business Efficiency: An Information Systems Perspective Using the Nursobah Model - Akhira Akhira; Muhammad Syahrani; Ahmad Soni Adiffa (International Journal of Artificial Intelligence Research, 2026)
Enterprise Resource Planning (ERP) has emerged as one of the most significant technological innovations supporting organizational digital transformation by integrating various business functions into a unified information system. Despite the increasing adoption of ERP across different industries, many organizations continue to experience implementation challenges related not only to technological complexity but also to organizational communication, stakeholder engagement, and strategic management. Consequently, successful ERP implementation requires a comprehensive approach that integrates technological infrastructure with managerial and communication dimensions